EFL Learners’ Perspectives on the Utilization of Ice Breakers in Grammar Class: Is It Necessary? - Muna, Hayatul; Mardhiah, Ainol; Juliana, Juliana; Setiyana, Rusma (Universitas Teuku Umar, 2024)
This qualitative study attempts to find out students’ perceptions on the utilization of icebreakers in grammar class. It broadly believes that better teaching and learning provide a likely classroom climate. EFL teachers employ plenty of strategies and activities to actualize successful language acquisition. Reliable icebreaker activities are one of the techniques that support EFL learners to gain a well-turned learning outcome, especially in Grammar. To take the sample, the researcher used purposive sampling, which Involved 12 students from the 3rd semester of English Department at the State Islamic Institute of Lhokseumawe. A questionnaire with Likert-scale solely shed light on the description of EFL learners’ perceptions of the use of icebreakers in grammar class. Moreover, the data analysis was done through some steps, namely, data collection, data display, and conclusion drawing or verification. Several bar charts were presented to illustrate the data. The result indicated that icebreakers became substantial activities in grammar class to organize not only linguistic and social factors but also psychological factors in language learning, such as boredom, anxiety, nervousness, and insecurity. Various kinds of applicable ice breakers implemented in grammar class stimulate students’ interest, foster their motivation and enthusiasm, and develop interpersonal skills. Thus, EFL Learners are ready to undergo the forthcoming lesson on grammar and have a positive learning experience. So, understanding of the subject matter improves. Finally, this study can be a powerful teaching reference for future research on similar topics.